LANGKAH-LANGKAH PEMERINTAH DALAM MENGANTISIPASI ISU PERUBAHAN IKLIM - Muhammad Dedy; Sapto Hermawan (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
This article discusses the issue of climate change that is happening in the world today. The government's focus in dealing with this is to develop a National Action Plan for Climate Change Mitigation and Adaptation. This strategy views climate change as a real thing and has an impact on Indonesia's financial and ecological changes. In its implementation, the RANMAPI promoted by the government still encounters various obstacles that make it difficult to achieve the targets that have been set. This article uses the method of induction and deduction with literature study techniques. The purpose of this article is to discuss the government's steps in anticipating the issue of climate change and evaluating the strategies that have been taken. The results and discussion in this article are reviewing government policies by conducting an appropriate evaluation system. The solution steps that can be taken by the government are: First, directing environmental and climate perceptions with the assistance of local organizations based on BMKG data support. Second, enacting a Government Regulation that regulates the Foundation for Implementation of Climate Change Adaptation. Third, changing monetary arrangements by highlighting financing assets for the implementation of climate change transformation programs. With thehelp of various existing components, the Indonesian people believe that the issue of climate change can be resolved through the execution of an ideal strategy program.